Hubungan antara Kadar Plumbum (Pb) dan Hipertensi pada Polisi Lalu Lintas di Kota Manado - Mery Bidangan Pasorong, Haripurnomo Kushadiwijaya, Nawi Ng, Vitalis Pribadi (Berita Kedokteran Masyarakat (BKM), 2007)
Background: Hypertension can be divided  into two types, i.e. primary and secondary hypertension. Risk factors related to incidence of essential hypertension, among others are age, sex, smoking, alcohol, obesity, inactivity and air pollution. Air pollution can derive from motor vehicles and air which contains plumbum (Pb). Pb may enter the body through inhalation, foods, drinks and absorption through skin. The effects of Pb for health are blood pressure elevation (hypertension), brain damage, neural damage, decrease of intelligence quotient inchildren, miscarriage and damage of male reproductive system. Population with high risk Pb exposure are traffic police working on the road.Objective: The objective of the study was to identify relationship between Pb level in the blood and prevalence of hypertension among traffic police in Manado Municipality.Method: The study used cross sectional design. Sample consisted of 192 subjects or study participants: 96 traffic police officers working on roads and 96 working at the office of Manado Capital City Police. Study participants were chosen using simple random sampling technique. Data were analyzed descriptively, using univariable and multivariable analyses.Result: The result of univariate analysis showed that Pb in blood had significant relationship (p<0.05) with incidence of hypertension (OR=6.50). The result of multivariate analysis showed that Pb in blood had significant relationship with incidence of hypertension (p<0.05). The value of OR=7.42 (95% CI 2.58-21.31) indicated that policemen having Pb level in blood = 6.27µg/dl had 7.42 times higher risk in suffering from hypertension than those with Pb level in blood < 6.27 µg/dl after being controlled with length of on duty, length of work, mother’s/ father’s history of hypertension, sports activities and smoking. Although after being controlled with length of on duty and length of work the relationship between Pb level in blood and incidence of hypertension was statisticallyinsignificant (p>0.05), by looking at the value of Odds Ratio (OR) it could be identified that traffic policemen working more than 8 hours/day had 2 – 2.4 times higher risk of suffering from hypertension than those working in the office. Mothers’/father’s history of hypertension, sports inactivities and smoking also increased risk of hypertension incidence among traffic policemen.Conclusion: There was relationship between Pb level in blood and incidence of hypertension after being controlled with length of on duty, length of work, mother’s/father’s history of hypertension, sports activities and smoking.Keywords: Plumbum (Pb) level, hypertension, traffic policeman